98 Improving use of co-ordinate my care electronic patient record at st christopher's hospice – completing the audit cycle. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Doyle, Christopher; Ross, Joy
Abstract : Introduction: Co-ordinate my care(CMC) is the pan-london electronic patient record system for palliative care patients. It facilitates sharing urgent care records across settings, linking services which patients may access(GP, ambulance, district nurses, palliative care). By creating records and working with local services to update records, we aim to improve 'joined up working' for our patients. Aims/objectives: To audit use of CMC for patients under the hospice including numbers of patient consented/records created, congruence of information recorded with hospice electronic records and access of records by emergency services. Methods: We conducted snapshot audits of records in december 2018, subsequent QI initiatives including staff training and integration of CMC reviews into MDM meetings, with re-audit December 2019. Each audit examined 200 patient records, 100 indicated as 'CMC record created' on our hospice system and 100 indicated to have no record. Patients were randomly selected; 40 from each service:Bromley community, bromley care co-ordination, croydon community, Lambeth/southwark/lewisham community and sydenham outpatients. Information was cross-checked against the live CMC record. Standards included: 90% of patients should have a CMC record, 95% should have documentation of consideration of CMC, 95% of CMC records should have resuscitation and ceilings of care decisions recorded with congruence between systems. We also recorded whether CMC records were accessed by OOH services. Results: Comparing data from our initial audit to the re-audit; 61% vs 73% of patients under our care were consented to have records created. Of these >95% had a live CMC record. For those not consented by us 220–40% had a live record across each of the 5 services. Between audits, numbers of patients with CMC records increased from 48–60% to 58–68%. Discussion of CMC with patients increased from 48–53% to 70–93%. Recording of DNAR status averaged >95%. Congruence of DNAR decisions was 82% with ceilings of care 61% congruent. Inclusion of hospice contact details varied across teams (30 to 74%). Records were accessed by out of hours services for 13 of these patients. Conclusion: Use of CMC is increasing with access to records by OOH services. Further QI initiatives to drive numbers and quality of records will be discussed with impact of OOH records accessed on patient outcome.